2021
DOI: 10.1007/s00262-021-02934-3
|View full text |Cite|
|
Sign up to set email alerts
|

Tumour draining lymph node-generated CD8 T cells play a role in controlling lung metastases after a primary tumour is removed but not when adjuvant immunotherapy is used

Abstract: Surgical resection of cancer remains the frontline therapy for millions of patients annually, but post-operative recurrence is common, with a relapse rate of around 45% for non-small cell lung cancer. The tumour draining lymph nodes (dLN) are resected at the time of surgery for staging purposes, and this cannot be a null event for patient survival and future response to immune checkpoint blockade treatment. This project investigates cancer surgery, lymphadenectomy, onset of metastatic disease, and response to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Several animal studies have shown that the primary site of tumor-specific T-cell generation is the lymph node draining the tumor [ 41 , 42 , 43 ]. A study carried out on murine models with resectable but micrometastatic NSCLC aimed to determine the impact of the resection of lymph nodes draining the tumor (spotted by infrared fluorescence) on the development of pulmonary metastases [ 44 ]. It has been shown that the median survival after surgery was statistically better in the group without lymph node resection than in the group with resection of lymph nodes draining the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Several animal studies have shown that the primary site of tumor-specific T-cell generation is the lymph node draining the tumor [ 41 , 42 , 43 ]. A study carried out on murine models with resectable but micrometastatic NSCLC aimed to determine the impact of the resection of lymph nodes draining the tumor (spotted by infrared fluorescence) on the development of pulmonary metastases [ 44 ]. It has been shown that the median survival after surgery was statistically better in the group without lymph node resection than in the group with resection of lymph nodes draining the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…These results could change the practice of segmentectomy in the future with systematic intraoperative confirmation by frozen section, guided by a successful identification of the sentinel lymph node. Finally, in the era of immunotherapy, the performance of a systematic lymph node dissection in patients whose sentinel lymph node is not invaded (confirmed with frozen analysis) must be put into perspective in view of the possibility of peri-operative effective immunotherapy treatment ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…This data highlights the TDLN as a key site of immune regulation and control over the tumor microenvironment; thus, expanded dissection of the said nodes may lead to immune impairment due to less antigen exposure and immune priming. Further murine data were generated ( 31 ) from a metastatic lung cancer model where the primary subcutaneous tumors were resected with associated draining lymph nodes (dLN) remaining intact, completely resected, or partially resected. The median survival after surgery was significantly shorter with complete dLN resection at the time of surgery (49 days) compared to when lymph nodes remained intact (>88 days; p < 0.05).…”
Section: Immunobiological Implications Of Lymph Node Resectionmentioning
confidence: 99%